2017
DOI: 10.1167/tvst.6.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the ON and OFF Contributions to the Flash ERG with the Discrete Wavelet Transform

Abstract: PurposeDiscrete wavelet transform (DWT) analyses suggest that the 20- and 40-Hz components of the short-flash photopic electroretinogram (ERG) are closely related to the ON and OFF pathways, respectively. With the DWT, we examined how the ERG ON and OFF components are modulated by the stimulus intensity and/or duration.MethodsDiscrete wavelet transform descriptors (20, 40 Hz and 40:20-Hz ratio) were extracted from ERGs evoked to 25 combinations of flash durations (150–5 ms) and strengths (0.8–2.8 log cd.m−2).R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…The corneal positive b-wave of the flash ERG is thought to involve ON- and OFF-bipolar cells 32 38 and transretinal currents that depolarize Muller cells. 4 , 39 Higher stimulus energies produce greater b-wave amplitudes and shorter implicit times, 40 light-adapted photopic b-wave implicit times are approximately 30 to 32 ms, about two times faster than dark-adapted implicit times (approximately 60 ms) but with a 4-fold smaller amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corneal positive b-wave of the flash ERG is thought to involve ON- and OFF-bipolar cells 32 38 and transretinal currents that depolarize Muller cells. 4 , 39 Higher stimulus energies produce greater b-wave amplitudes and shorter implicit times, 40 light-adapted photopic b-wave implicit times are approximately 30 to 32 ms, about two times faster than dark-adapted implicit times (approximately 60 ms) but with a 4-fold smaller amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the component waveforms of the flash ERG have also been provided through time-frequency analyses with discrete wavelet transforms. 37 , 38 , 51 In a purely linear system, the voltage distributions are expected to be Gaussian. Instead, we found that the means of the fitted Gaussians shifted with changing luminance and contrast.…”
Section: Discussionmentioning
confidence: 99%
“…In the full-field ERG, DWT has been shown to reveal additional contributions as shown by Gauvin et al [ 26 ]. For example, Gauvin et al [ 25 , 47 ] were able to show a strong correlation between DWT descriptors and different parts of the full-field ERG such as the a -wave, the b -wave and also oscillatory potentials at 80 and at 160 Hz [ 26 ]. Thus, DWT offers a promising tool, in particular as the response to the global flash mfERG waveform does not show typical a - or b -waves due to the adaptive properties of the stimulus response.…”
Section: Discussionmentioning
confidence: 99%
“…Another improvement might be to include the Hölder exponent, as proposed by Gauvin [ 25 , 49 ] which characterizes the complexity of the waveform and was able to identify electrophysiological changes in the ERG prior to changes in the visual field in retinitis pigmentosa [ 49 ]. In addition, the use of scalograms [ 24 , 25 , 47 ] that summarize the particular contribution of individual coefficients over time may improve understanding of disease.…”
Section: Discussionmentioning
confidence: 99%
“…This approach suggests the activity of the retinal On-pathway to be related to a 20 Hz component of the photopic ERG, while the Off-pathway activity is reflected by a 40-Hz component. This finding was based on the fact that 20 and 40 Hz components of the photopic b-wave are selectively attenuated in case of imbalanced dysfunction of the On- and Off-pathways in some diseases [ 32 ], confirmed with the DWT of the photopic On–Off ERGs [ 33 ]. Since the photopic On–Off ERG is potentially valuable ERG method in animal studies, researchers should be aware that positive On- and Off-responses, as those in humans, can only be recorded in some non-human primates, while On- and Off-responses with electronegative waveform are present in rodents including mice and rats [ 34 ].…”
Section: Appendixmentioning
confidence: 98%